Effect of Death Mulching Methods to Weed Coverage in Mandarin Orchard - Onur Kolören; Feyzullah Nezihi Uygur (Turkish Journal of Agriculture: Food Science and Technology)
The possible use of three different thickness black geotextile materials (GEO-50, GEO-100 and GEO-150) , the new control methods for our country, compared with weedy check among of the rows and using herbicide (Glyphosate), mowing, black polyethylene with weedy check on the rows have been investigated for controlling of weeds which is a considerable problem of tangerine orchard. Experimental randomly plots were arranged by considering complete block design with five replications on the rows treatment. Mulch materials were applied apart for width of 160 cm on the rows. When weed coverage (%) reached 10-15%, herbicide (Glyphosate) was applied with 600 cc/da. Mowing was applied when weed lenght and coverage (%) reached 10-15 cm and 10-15, respectively. Weed coverage (%) and numbers were counted in 15 days intervals at the quadrats for all plots. The results of the studies for tangerine orange 4 years old showed that mulching with black geotextile and polyethylene were more supressed than the other control methods on the row. Average weed coverage (%) was found 56.09% in control (weedy), 24.66% in mowing, 11.05% in herbicide, 3.09% in black polyethylene, 2.78% in GEO-50, 0.87% GEO-100 and 0.76% JEO-150, respectively. As observed weed coverage (%), the similar result was found for weed number in black geotextile treatments.